KETIKA YOGA SEBAGAI GAYA HIDUP - I Wayan Budi Utama; Ida Bagus Suatama (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2018)
Asana Yoga has now undergone a shift from a system of spiritual philosophy to a traded lifestyle. This can happen because of the market ideology that enters various joints of people’s lives. As a result Yoga is now a mass culture that is produced with a capitalistic purpose. This paper is the result of research with the approach of sociology by using social theories. Data analysis was done by descriptive interpretative.